A Systems study on the Energy Research and Development Division of the Philippine National Oil Company - Diaz, Yolanda; Inciong, Rodrigo Jr; Rodriguez, Gerardo; Salvacruz, Vivien; Suganob, Perlita (College of Engineering, 1984)
As a requirement of our terminal course IE 55, Total Systems Design we conducted a total systems study on the Energy Research and Development Center. The system studied was the Program Planning and Control System. The study was undertaken to provide us with the training in planning and designing total systems set in the real world. In so doing, we could identify problem areas in the system and present the best solution among the feasible alternatives generated for the problem. ERDC, a research arm of the Philippine National Oil Company was envisioned to carry out the research and development activities to enhance efficient utilization of conventional fuels and develop economically competitive substitutes for conventional fuels. Their activities are geared towards commercialization of these energy technologies. To carry out its objectives, ERDC develops energy programs, which are implemented by the R & D departments of the center. The system we chose for our study is the planning and control of these technology programs. Planning the technology programs starts with the Program Planning Committee choosing and prioritizing technologies from a list of energy technology programs prepared and evaluated by the Project Monitoring and Evaluation section. To carry out the program, the R & D sections of ERDC submit project proposals to PME which evaluates those using techno-economic criteria. The PPC then approves disapproves the proposals taking into consideration the evaluation of PME. While studying the system we discovered several problem areas. First, some researchers cannot get needed information from within ERDC itself. This is evidenced by the duplication of research works, interdepartmental gripes and researchers going outside ERDC to get the needed materials when they already exist within ERDC. This was caused by the improper cataloging of research materials and the refusal of some researchers to lend their research materials to fellow researchers. The second problem involves the inability of the monitoring group to get sufficient data for a complete program report. This was traced to the refusal of some R & D personnel to disclose all needed information and the lack of authority on the part of the monitoring group to demand the information. The last problem deals with the efficiency of monitoring the progress of the projects. Sometimes the monitoring of the projects is too frequent thereby irritating the R & D personnel. This led to the refusal of the R & D personnel to disclose all information needed by the monitoring group. In evaluating the alternatives we used the interaction matrix to determine the relationships between the objectives, criteria, key variables or alterable, needs and the constraints on the performance of the system. The interaction between the needs and the criteria gave us the most interactive needs which were subsequently screened by the constraints. Affected alterable were identified through the interaction of those needs and the objectives. Actual evaluation was accomplished by comparing the relative weights of the constraints and the degree of interaction of each need. The problem on inavailability of research materials within ERDC itself, we recommend an extended library system. This system uses the library as the information center which will provide all available references and research papers for the ERDC staff. The library's facilities are extended by using the collection of reading materials from every section and keeping them in their respective section. Thus, all references and research materials will be properly catalogued. We integrated the next two problems because they both deal with greater control of project implementation. For this we proposed a new system which embodies a more responsive monitoring procedure. This requires a monitoring system which is tailored to the needs of each project.